Hubungan Tingkat Kecemasan dengan Hipertensi pada Lansia di Wilayah Kerja Puskesmas Andalas Kota Padang - Sarah Dzakirah; Ida Rahmah Burhan; Husni Husni (Lembaga Pengembangan Kinerja Dosen, 2025)
The elderly is among the most vulnerable groups in society due to progressive biological decline that weakens physical resistance, making them prone to chronic diseases such as hypertension. Hypertension is one of the most common multifactorial disorders in older adults, and its severity may be influenced by anxiety, which stimulates the sympathetic nervous system and increases blood pressure. This study aimed to examine the relationship between anxiety levels and hypertension among the elderly in the working area of Andalas Health Center, Padang City. An analytic study with a cross-sectional design was conducted involving 81 elderly participants diagnosed with hypertension, selected through accidental sampling based on inclusion and exclusion criteria. The Geriatric Anxiety Scale (GAS) was employed as the research instrument, while data analysis used the Chi-square test. Results showed that the majority of respondents experienced mild anxiety (67 respondents, 82.7%) and uncontrolled hypertension (54 respondents, 66.6%). Statistical analysis revealed a p-value of 0.534, indicating no significant association between anxiety levels and hypertension in the elderly population studied. These findings are consistent with several previous studies reporting that the relationship between anxiety and blood pressure in the elderly is often inconsistent, largely due to other risk factors including age, gender, low physical activity, comorbidities, and poor adherence to antihypertensive treatment. The implication of this study highlights the necessity of a holistic approach to hypertension management in the elderly, addressing not only psychological aspects but also lifestyle modification, treatment adherence education, and strengthening public health programs. Therefore, this research is expected to serve as input for health workers at community health centers to improve strategies for preventing and controlling hypertension in elderly populations.